SHORT REPORT: THE ACTIVITY OF PAMAQUINE, AN 8-AMINOQUINOLINE DRUG, AGAINST SPOROZOITE-INDUCED INFECTIONS OF PLASMODIUM VIVAX (NEW GUINEA STRAINS) - SWEENEY, ANTHONY W; BLACKBURN, CHARLES R. B; RIECKMANN, KARL H (The American journal of tropical medicine and hygiene, 2004)
It was reported in 1946 that the administration of pamaquine during the incubation period delayed but did not prevent primary attacks of a New Guinea strain of Plasmodium vivax malaria. The observation that none of the four test subjects in this study had relapses has not previously been published and may have important implications for the evaluation of other 8-aminoquinoline compounds against relapsing vivax malaria.